Spatiotemporal variations in the sound production of snapping shrimps in Poblacion Marine Sanctuary, Liloan, Cebu - Cayon, Jericho James C. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Soundscape ecology is used to describe the relationship between a landscape and its sound composition. Acoustics provide information on diurnal, lunar, and seasonal sound patterns. The most distinct and intense noise is produced from coral reefs where snapping shrimps dominate coral reef soundscapes. The sounds from these snapping shrimps exhibit correlations with various acoustic indices such as the acoustic complexity index (ACI). However, studies on spatiotemporal variations in the coral reef in Liloan, Cebu are still limited given that studies previously conducted at the site relied on a single recorder deployed to characterise the reef soundscapes. Furthermore, no attempts have been made to quantify their sound production output. It is vital to explore whether a single recorder would define the entire soundscape characteristic of a reef site or whether the sound recorded would vary from multiple adjacent site recordings. This study used two simultaneous data recordings from previous studies deployed in adjacent locations analysed with an automatic snap detection method. Results showed that snapping shrimps sound production patterns did not vary significantly in both diel and lunar scales. However, significant differences were found between daytime and nighttime snapping patterns across different lunar phases. Acoustic complexity index was also found to be significantly different across all lunar phases between the two locations and was correlated with snapping shrimp sound production showing a slight negative correlation in one site and a strong negative correlation on the other. This study is an attempt to quantify the coral reef soundscapes characteristics in Liloan, Cebu as well as to give insights on future methods of data collection.